Eurocities and Their "Sisters": How Are They Close to Each Other? - Tuzin Baycan Levent; Seda Kundak; Aliye Ahu Gulumser (European Regional Science Association (ERSA), 2006)
The globalization process has led to the emergence of network of cities in which the cities have become more integrated to the new world system. 'Eurocities' or 'Sister Cities' are among the well known examples of network of cities which provide interaction and cooperation of the cities at the regional and global level. The 'sister city movement' can be defined as a further step of international relationships of the cities at the municipality level which is based on understanding the cultures of each other and aims to create common values. Additionally, sister city relationship provides international trade and economic development between two countries at the local level. Empirical findings show that there are 3 phases of sister city movement: i) the associative phase, ii) the reciprocative phase, and iii) the commercial phase. In this process, municipalities or local authorities have become 'entrepreneurs' in order to contribute to the economic and social dynamisms of cities. The present study investigates the relationships of Eurocities with their sister cities from the perspective of the development level or the degree of the relationship. Which factors are important in improving the mutual relationship? Which factors determine the development phases of the relationship? Under which conditions the mutual relationship creates business opportunities and reaches to the level of economic cooperation? What are the success measures of city-to-city affiliation? The study aims to compare and evaluate the current sister cities relationships of Eurocities on the basis of the actual performance in cultural dialogue, benchmarking and commercial activities. The data and information used for comparison and evaluation are based on extensive survey questionnaires filled out by relevant departments or experts of municipalities in Eurocities. As a rather novel methodological contribution, a recently developed artificial intelligence method, i.e. rough set analysis, is deployed to assess and identify the most important factors that are responsible for successes and failures of the relationships between sister cities.
Keywords: 330